Impact of innovation on economic growth in Balkan countries - Albina Hysaj; Kriselda Sulaj (Agora International Journal of Economical Sciences (AIJES), 2024)
Innovation plays a crucial role in the daily activities of economic units and its impact extends to the macroeconomic level as well. After the last pandemic, firms and even nations are aiming to adopt the new reality. They are employing advanced technology to develop innovative products and approaches for customers and markets. This study analyzes the impact of innovation on economic growth in Balkan Countries by using annual data for the period between 2011 and 2022. This study uses the individual pillars of the Global Innovation Index as the explanatory variables of GDP Growth rate. Through a panel data analysis, the findings of the study suggest that creative output and infrastructure have a positive significant effect on the GDP growth rate, while the effect of institutions is negative. The test employed failed to prove any impact of other pillars of innovation on economic growth meaning that the impact of other pillars is still insignificant. The findings of this study may serve policymakers to work on the direction of enhancing the impact of all innovation pillars on the economic growth rate.
Keywords: 330